Determinación de la procedencia de los animales comercializados en la feria del cantón Guaranda provincia Bolívar. - Aroca Izurieta, Carlos Enrique (2021)
The determination of the commercialization channels of the cattle in the city of Guaranda, Bolívar province, differentiate the forms of negotiation practiced in the local market, the forms of transportation, the main actors that intervene in the commercialization process, are the intermediary merchants The methodology used was through visual inspection and the application of surveys directed at the actors in the commercialization chain, such as introducing producers and intermediary merchants. The main results include the level of education of the producers, with 55% being primary while 38% secondary and 7% with higher education with a probability of 0 (NS). Traders use the previous physical condition to improve the price of cattle reaching 78%. Most actors resort to a credit for special productive and commercial activity issued by banks and cooperatives. Bovines have as final destination in the same town in the province with 48%, with mobility to other provinces is important 16% Riobamba, 16% Caluma, 15% Ambato 7%, Chimbo San Miguel and San Pablo probability of the value of 0 (NS) etc. The animals mostly exploited and sold are the meat-type crossbreds and dual purpose achieved, more phenotypically evaluated bovines that predominate in the area are the Holstein breed with 34%, 30% Brown Swiss breed, 13% Jersey, 10% Red Holstein , 8% mestizo, and 5% other races with a probability of 0 (NS). The resources obtained from the productive and commercial activity are used 62% in food, 17% in education, 11% in housing and 10% reinvestment, of livestock production, probability of value 0 (NS) in this research we have taken into account that most of the producers are dedicated to raising different breeds of animals etc.